Analisis Framing Caleg Selebritis di Media Online pada Pemilu 2024 - Sugiarto Sugiarto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Celebrities have taken part in Indonesian elections since 1971. They were employed in populist political party recruitment operations. They frequently serve as canvassers for political parties with an interest in reaching the minimal threshold. The artist is convinced that he will be able to pass being elected as a member of the legislature because of his popularity. This study examines how celebrity candidates for the 2024 election are framed in online media. The Entman framing analysis model is employed for the analysis. Republika.co.id, Kompas.id, and Tribunnews.com are the web publications used in this study. Based on Problem Identification, even though celebrity candidates do not have the ideal qualities and capabilities to become members of the legislature, there are still many celebrity candidates in every election. Causal Interpretation, from this phenomenon is that the process of regeneration and regeneration in all political parties is not going well, on the other hand political parties need a machine to gain votes to pass the threshold of sufficient votes. So that the Moral Judgment of this problem is that political parties are more focused on improving the performance of their members and celebrity candidates with good quality and capability can become the choice of political parties. The Treatment Recommendation that can be offered is to provide celebrity candidates with political education by political parties, bearing in mind that the functions, duties and position of the legislature are one of the strategic pillars of power for a country.